Mathematical simulation and life cycle assessment of blast furnace operation with hydrogen injection under constant pulverized coal injection. (1st January 2021) - Tang, Jue; Chu, Mansheng; Li, Feng; Zhang, Zedong; Tang, Yating; Liu, Zhenggen; Yagi, Junichiro
Abstract: Considering the serious coal restriction in some areas of China and enhancing the utilization of H2 in blast furnace, the mathematical simulation and life cycle assessment of blast furnace (BF) operation with H2 injection under a constant pulverized coal injection were studied in this work. It was shown that the thermal compensation by increasing oxygen enrichment was to keep a stable adiabatic flame temperature after H2 injection. When the H2 injection rate was 120 m 3 per ton hot metal (m 3 /tHM), the oxygen enrichment rate was 10.38%, and the H2 concentration in raceway was enhanced to 15.23%. With the increasing H2 injection, the reduction of burden was promoted and the cohesive zone became thinner and its position moved down, contributing to the good permeability. Meanwhile, the amount and temperature of top gas decreased, the utilization rate of CO increased while that of H2 decreased resulting from several gaseous reactions, and the indirect reduction was intensified but the direct reduction was weakened in the stack of BF. When the H2 injection rate was 120 m 3 /tHM, the productivity increased by 28.8%, the coke rate decreased by 12.87%, and the pressure drop decreased by 19.38%. Through life cycle assessment, it was obvious that the total environmental impacts and CO2 emission during the whole ironmaking were both cut down, with the evident decreases from the 9.13E-11 to 8.11E-11 and from 1956.9 kg/tHM to 1854.64 kg/tHM respectively corresponding to the injection rate from 0 to 120 m 3 /tHM. Moreover, the environmental improvements for H2 injection were mainly achieved through the two processes of BF and coking, and the impact type of acidification had the most significant effect on the total environmental impact. With the increasing H2 injection rate, the contribution on the total environmental impact by impact type was descended by acidification, eutrophication, and followed by climate change.